Psychological flourishing: Validation of the French version of the Flourishing Scale and exploration of its relationships with personality traits. (January 2016) - Villieux, Arnaud; Sovet, Laurent; Jung, Sung-Cheol; Guilbert, Laure
Abstract: The purpose of this paper was to test the psychometric properties of the French version of the Flourishing Scale (FS, Diener et al., 2010) as a means to investigate the relationships between psychological flourishing and Big-Five personality traits. Participants for the study were 403 French sophomore students. Confirmatory factor analyses provided support for a single construct and an invariant structure of FS. Results revealed good fits in convergent validity through well-being related variables and the scale demonstrated satisfactory internal reliability. Correlation analysis indicated that conscientiousness had the highest positive correlation with psychological flourishing; extraversion and agreeableness were also positively related, whereas neuroticism was negatively related. A low positive correlation was also observed between FS and openness. Overall, personality traits accounted for 30% of variance in predicting psychological flourishing. Consistent with previous studies of associations between personality traits and well-being, our findings may well extend the concept of psychological flourishing. Highlights: Psychological flourishing incorporates subjective and psychological well-being. Relationships between personality traits and psychological flourishing were explored. The psychometric properties of the Flourishing Scale — French version were examined. Conscientiousness, extraversion and neuroticism related to psychological flourishing. Personality traits predicted 30% of variance for psychological flourishing.